Novel Target Antigens of the Variant-Specific Immune Response to Plasmodium falciparum Identified by Differential Screening of an Expression Library - Le Scanf, Cécile (American Society for Microbiology, 1999)
A primary infection by the Plasmodium falciparum Palo Alto O and R antigenic variants induces a variant-specific immunity in the Saimiri sciureus monkey. We have shown that these variants express distinct PfEMP1 antigens and differ in their levels of expression of additional antigens, including two conserved erythrocyte membrane-associated proteins, HRP1 and PfEMP3. To identify the antigens eliciting a variant-specific response, we conducted a differential screening of a λgt11 library with variant-specific sera. We report here the analysis of the 46 anti-R-specific clones. Two specific targets of the anti-R response were identified: (i) PfEMP3, suggesting that immunogenicity of this antigen is modulated by its relative abundance in different variants, and (ii) Asn-rich motifs. Most anti-R-specific clones, derived from so-far-undescribed genes, were detected by a cross-reaction on poly(Asn) stretches, as indicated by elimination of the signal after absorption on Asn-rich sequences. Reverse transcription-PCR (RT-PCR) showed that expression of the gene defined by clone 13 was R specific. Pepscan analysis of clone 13 identified three Asn-rich polypeptides and one unique peptide reacting specifically with antibodies eluted from the R-infected erythrocyte surface. Antisera raised to the unique peptide reacted with an R-specific protein. Attempts to demonstrate that clone 13 was derived from a var gene by using PCRs combining clone 13 and var-derived primers were unsuccessful. The var genes expressed by O and R parasites were identified not by this strategy but by RT-PCR with var-specific primers. This work has provided novel insights into immunity to antigenic variants and has identified a novel gene switched on during antigenic variation.